Modeling of ground deformation in the vicinity of the Soufriere Hills volcano - Shardakov, Igor Nikolaevich; Fedorova, Varvara Anatolievna; Glot, Irina Olegovna; Melnik, Oleg Eduardovich (Computational Continuum Mechanics, 2014)
Ground deformation monitoring in the vicinity of active volcanoes is one of the main research methods of their control. A necessary component of the monitoring system is a mathematical model of the strain state of rock mass in the vicinity of the volcano. The paper presents the results of modeling the Earth’s surface deformation in the vicinity of the Soufriere Hills volcano (the Caribbean island of Montserrat) taking into account the structure of its magmatic system, the rock mass structure, and the pressure distribution in the volcano magma chamber-conduit. It is shown that deep igneous processes produce axisymmetric surface deformation response. Processes that occur in the sub-surface area cause deformations reflecting the morphological features of this area. Based on the developed mathematical model, the concept of deformation monitoring system using fibre Bragg gratings sensors has been put forward. The model reflects the characteristic features of quasi-static deformation processes, i.e. phenomena that precede an active phase of volcanic activity. The mathematical model of deformation processes of hard rock in combination with the mathematical model describing the hydrodynamics of magmatic fluids allows us to interpret sensor data enabling monitoring. Analysis of the interpretation results makes it possible to predict the onset of an active phase of volcanic activity. The monitoring system can provide adequate information about the changes in the deformation field caused by volcanic processes in the vicinity of the volcano.